Physico-chemical and sensory characteristics of red oncom, a traditional fermented food from Indonesia, based on the variability of ingredients and processing steps - Aji Mustaq Firoh; Joncer Naibaho; Sugiyono; Christofora Hanny Wijaya (Applied Food Research)
Red oncom, a traditional fermented food from Indonesia, was produced differently using various ingredients and unstandardized production processes. The study aimed to evaluate the influence of raw materials and production processes on the physicochemical and sensory characterization of red oncom collected from nine different producers in three different regions. The study showed that there are three different categories of red oncom varied depending on the ingredients such as peanut press cake, okara, and tapioca waste. In addition to processes, the variability in inoculum preparation, ingredient preparations, and incubation period were identified. Okara flour generated a higher moisture content, soft and compact texture. Sensory profiling revealed that oncom made of okara flour had a higher intensity of musty aroma, beany aroma, orange color, red color, and sour aftertaste attributes. The soft and compact texture and fully covered mycelium of Neurospora fungi that gave an even surface orange color in red oncom made from okara was preferred by the panelists. The use of peanut press cake resulted in red oncom with higher fat content, a hard texture, and a higher intensity of nutty aroma and bitter taste attributes. The hard texture and a higher intensity of bitter taste caused red oncom made from peanut cake to be less preferred by panelists. In conclusion, the characteristic and chemical composition of red oncom varied depending on the ingredients, processes, and region.